Comparison of Cost and Time Efficiency Between Ruspin Houses and Conventional Houses Based on BIM Models - Rizka Aprilia Sari; Bagyo Mulyono; Redityo Januardi (Jurnal Ilmiah Dinamika Rekayasa, 2026)
The rapid population growth in Indonesia has created an imbalance between housing demand and supply, resulting in a significant housing backlog. Conventional construction methods, which are still widely applied, face limitations such as inefficiency, excessive waste, and long completion times. Prefabricated construction offers an alternative solution, one of which is the Rumah Unggul Sistem Panel Instan (RUSPIN) developed by the Ministry of Public Works and Housing (PUPR). This study aims to compare cost efficiency, time efficiency, and cost–time simulations between RUSPIN and conventional houses using a Building Information Modeling (BIM) approach. A comparative study based on secondary data was conducted by designing identical type-39 house prototypes for both methods. Modeling was performed with Autodesk Revit (3D), while scheduling simulation and cost–time integration were carried out using Autodesk Navisworks (4D and 5D). The results show that conventional construction requires Rp 126.301.865 and 71 days, while RUSPIN construction requires only Rp 117.550.753 and 58 days. This indicates a cost saving of Rp 8,751,112 (6.93%) and a time reduction of 13 days (18.31%). These findings demonstrate that the RUSPIN system is more efficient than conventional methods in both cost and construction time.